Dendrimers: Role in Novel Drug Delivery - Mittal P.; Kapoor R.; Mishra B. (My University, 2025)
Dendrimers are nanosized, symmetrical molecules in which a small atom or group of atoms is surrounded by the symmetric branches known as dendrons. Due to their complex structures, their physical and chemical properties get changed. They grow outwards from the core shell, which further reacts with monomers having one reactive or two dormant molecules. Their unique characteristics, viz. hyperbranching, well-defined spherical structure, and high compatibility with the biological systems, are responsible for their wide range of applications including medical and biomedical area. Particularly, their three-dimensional structure can incorporate a wide variety of drugs to form biologically active drug conjugates. In this chapter, we have included the details on the synthesis, mechanism of drug encapsulation in dendrimers, and their wide applications in drug delivery. © 2021 Scrivener Publishing LLC.